Genetically diverse yet morphologically conserved: Hidden diversity revealed among Bornean geckos (Gekkonidae: Cyrtodactylus). (20th April 2021) - Davis, Hayden R.; Das, Indraneil; Leaché, Adam D.; Karin, Benjamin R.; Brennan, Ian G.; Jackman, Todd R.; Nashriq, Izneil; Onn Chan, Kin; Bauer, Aaron M.
Abstract: The appreciation of cryptic biological diversity, and the pace at which it is recognized, has greatly increased with the use of molecular systematic techniques. The gekkonid genus Cyrtodactylus Gray, 1827 is one example of a group that has undergone a particularly rapid increase in recognized diversity due to molecular systematic studies. Many of these new species result from recognizing closely related but diagnosable lineages into sister taxa. Our study implements a multi‐faceted approach to delimit cryptic Cyrtodactylus lineages on the Southeast Asian island of Borneo using morphological, ecological, and multilocus genetic data. We use multiple species delimitation models to assess species boundaries and identify clades that warrant further investigation. Unlike most morphologically cryptic species that have recently diverged, we find evidence of cryptic lineages being polyphyletic. Using multivariate statistical analyses, we show minimal phenotypic distinction between putative cryptic species within the C. pubisulcus complex. Despite not finding morphologically diagnostic characters, we demonstrate strong evidence for the specific recognition of C. hantu sp. nov. and C. miriensis sp. nov., which are currently considered conspecific with C. pubisulcus, from Sarawak, Malaysia. Our new concept for C. pubisulcus restricts the geographic range of the species to specific regions in western Sarawak, Malaysia, thus underscoring the need to conserve the limited remaining habitats of these species, as well as the considerable undescribed diversity across Borneo. Abstract : We implement a multi‐faceted approach to delimit morphologically cryptic gecko species in the genus Cyrtodactylus on the Southeast Asian island of Borneo. Despite lacking clear diagnostic morphological or ecological features among the cryptic lineages, we use multilocus molecular genetic data and species delimitation methods to show that C. pubisulcus is a polyphyletic group comprising at least three distinct species. As such, we describe two new species and discuss implications and difficulties associated with recognizing cryptic diversity.